Comparison of electrolyte and acid-base balances of Dorper breed ewes between single and twin pregnancies - Santarosa, Bianca P. [UNESP]; Dantas, Gabriela N. [UNESP]; Ferreira, Danilo O.L.; Carvalho, Marina G. [UNESP]; Rodrigues, Mirian; Pereira, Priscilla F.V.; Silva, Andreza A.; Gonçalves, Roberto C. [UNESP] (FapUNIFESP (SciELO), 2019)
During pregnancy there are modifications in the metabolic profile of sheep that may predispose to the occurrence of metabolic disorders, of which pregnancy toxaemia (PT) is highlighted. Blood gas analysis is detects changes in acid-base and electrolyte balance effectively. The objectives of this study were to study the acid-base and electrolyte balance of sheep during gestation and in the immediate peripartum (up to 48 hours postpartum), comparing single gestation with twins. Sixty healthy sheep of Dorper breed, two to five years old were raised in a semi-intensive system and were divided in two experimental groups: Group 1: 30 ewes, with ultrasonographic diagnosis of single fetus gestation; Group 2: 30 ewes, with ultrasonographic diagnosis of twin pregnancy. The experimental moments were defined as: MI-immediately after artificial insemination (control); MG30 - 30 days of gestation; MG90 - 90 days of gestation; MG120 - 120 days of gestation; MG130 - 130 days of gestation; MG140 - 140 days of gestation; MP - lambing; MPP1 - 24h postpartum; MPP2 - 48h postpartum. At all times 1mL of blood was collected per jugular vein puncture for blood gas evaluation in a portable equipament (I-Stat). The pH, carbon dioxide pressure (PCO2), bicarbonate (HCO3 –), base excess (BE), sodium (Na+), potassium (K+), chloride (Cl–), ionized calcium (Ca+2), lactate, anion gap (AG) were mensured and strong ion difference (SID) were calculed. This work showed that there were changes in acid-base and electrolyte balance in pregnant ewes, due to the decrease in BE, HCO3 –, TCO2 and increase of lactate and AG during gestation, but the pH remained normal and did not present any difference among moments in both groups. Comparing the groups, single-gestation ewes presented higher alkaline expenditure at delivery than twin-gestation, evidenced by lower levels of BE and HCO3 –. Lower Na+ levels were observed in prepartum; drop in K+ values with advancing gestation; hyperchloremia and hypocalcemia during gestation according to the reference standards for species; decreased iCa+2 levels in the final third of gestation in both groups. It was concluded that the ewes of this study were healthy until the last moment analyzed (48h postpartum), although have shown greater consumption of the alkaline reserve in the peripartum, being more explicit in the single gestation animals. In addition, this situation can be physiological and result in increased energy demand during gestation, more exacerbated by peripartum.
Keywords: Acid-base; Blood gas analysis; Dorper breed; Electrolyte; Ewes; Metabolic diseases; Ovine; Pregnancy; Sheep; Small ruminants; Twin pregnancies